Karakterisasi secara Morfologi Abnormalitas Embrio Somatik Kelapa Sawit (Elaeis guineensis Jacq) dari Eksplan Daun - Nesti F Sianipar; Gustav A Wattimena; Hajrial Aswidinnoor; Maggy Thenawidjaya S; Nurita Toruan-Mathius,; Gale Ginting (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2007)
Morphological Characterization on Abnormalities of Oilpalm(Elaeis guineensis Jacq) Embryo Somatic Generatedfrom Leaf Explant. Nesti F. Sianipar, Gustav A.Wattimena, Hajrial Aswidinnoor, Maggy ThenawidjayaS., Nurita Toruan-Mathius, and Gale Ginting. Somaticembryogenesis is the development of somatic cells to form astructure alike zygotic embryo direct or indirectly. Somaticembryos from young leaf explants could be induced fromprimary callus formed surrounding the palm-leaf rib. Embryogeniccallus will develop to be somatic embryos whichgrew nonuniformly. Embryo somatic growth pattern ofglobular, asymmetric heart shape, and cotyledon ary stageproduced different morphological variation. Morphologicalvariability of in vitro somatic embryos could be due to highapplication of growth regulator 2,4-D at the beginning ofinitiation, subculture frequency, loaded cells, and polysomiccells from certain tissues. From the three clones used,which were clone 638, 636, and 558, there were differentvariation at each step of development stages, groupingmorphologically into normal and abnormal based on thedevelopment of somatic embryos. The percentage of abnormalityfrom the three clone used was clone 27% (638), 30%(636), and 46% (558). The normal somatic embryos at globularstage were round and bipolar shaped; while the abnormalembryos were oval and no bipolar. At heart-shape stage,the normal somatic embryos had symmetrical polarized surface;while the abnormal embryos had asymmetrical polarizedsurface. At the cotyledon stage, the normal embryoshad monocot-tyledon; the abnormal ones were more thanone cotyledon.